Factors prompting in technology adoption of cashew farmers: Case of Eastern dry zone of Sri Lanka - Parththini, K.; Umashankar, K. (Sabaragamuwa University of Sri Lanka, 2022)
Introduction The economy of Sri Lanka continues to be dominated by small holder-agriculture and is highly dependent on the import-export economy. Presently, Cashew has gained the status of a commercial crop through technological advancements concerning propagation, production management and mechanized processing. Cashew produced in Sri Lanka is not sufficient to meet local consumption as well as export. The annual production of Cashew is estimated to be around 10000MT – 12000 MT (Sri Lanka Cashew Corporation, 2016). Cashew is imported in large quantities from India and is re-exported with value addition to address the inadequacy. It is expedient; therefore, existing plantations have to be managed efficiently for increased productivity, and fresh plantations have to be established to increase production substantially. Thus, new technology and management practices must be adopted to enhance the productivity of plantations. Cashew Corporation introduces new technology and management practices extensively. In Sri Lanka, cashew is observed to thrive and flourish in significant ground stretches in the Dry and Intermediate Zones. Cashew cultivation is prominent in Puttalam, Kurunegala, Anuradhapura, Hambantota, and Batticaloa. As far as Sri Lanka is concerned, removing the obstacles in increasing the productivity, enhancing the knowledge and skill of the farmers, and eliminating the hindrances in adopting technology in the industry, the quantity of cashew produced could be increased substantially. Hence, this study considered determining the extent of technology adopted relevant to cashew cultivation and identifying the socio-economic and demographic factors influencing the adoption of the technology in the Eastern dry zone of Sri Lanka